2008
DOI: 10.1073/pnas.0808393105
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin downregulation attenuates ischemic cardiac remodeling through enhanced resident precursor cell differentiation

Abstract: We analyzed the effect of conditional, ␣MHC-dependent genetic ␤-catenin depletion and stabilization on cardiac remodeling following experimental infarct. ␤-Catenin depletion significantly improved 4-week survival and left ventricular (LV) function (fractional shortening: CT ⌬ex3-6 : 24 ؎ 1.9%; ␤-cat ⌬ex3-6 : 30.2 ؎ 1.6%, P < 0.001). ␤-Catenin stabilization had opposite effects. No significant changes in adult cardiomyocyte survival or hypertrophy were observed in either transgenic line. Associated with the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
142
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(155 citation statements)
references
References 29 publications
10
142
3
Order By: Relevance
“…Thus, we suggest that by inducing IGF1 and its muscle-specific splice variants, AR promotes the growth of muscle by activating the b-catenin pathway. Downregulation of b-catenin attenuates myocardial remodeling by promoting precursor cell differentiation, while upregulation induces precursor cell proliferation during muscle regeneration (Otto et al 2008, Perez-Ruiz et al 2008, Zelarayan et al 2008. Thus, these data are consistent with the current understanding of b-catenin in muscle remodeling.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, we suggest that by inducing IGF1 and its muscle-specific splice variants, AR promotes the growth of muscle by activating the b-catenin pathway. Downregulation of b-catenin attenuates myocardial remodeling by promoting precursor cell differentiation, while upregulation induces precursor cell proliferation during muscle regeneration (Otto et al 2008, Perez-Ruiz et al 2008, Zelarayan et al 2008. Thus, these data are consistent with the current understanding of b-catenin in muscle remodeling.…”
Section: Discussionsupporting
confidence: 80%
“…77 Following experimental myocardial infarction in the mouse, b-catenin depletion attenuated post-infarct left ventricular remodeling, and significantly improved left ventricular function and survival. 80 Huang et al 81 demonstrated an association between Wnt signaling and post-infarct cardiac remodeling in aged mice. The cardiac detrimental role of Wnt/b-catenin signaling was further confirmed by the fact that b-catenin knockout attenuated phenylephrine-induced hypertrophy and upregulation of fetal genes in cardiomyocytes.…”
Section: Implications Of Wnt Signaling In Cardiac Pathologic Conditionsmentioning
confidence: 99%
“…Consistently, inhibition of reactivated Wnt signaling has been shown to attenuate the hypertrophic responses (12)(13)(14). Although much has been studied about the role of Wnt signaling in cardiac hypertrophy and infarction, the regulatory mechanisms of Wnt signaling in cardiac remodeling is not fully understood.…”
Section: Discussionmentioning
confidence: 93%
“…Wnt signaling plays diverse roles in the control of proliferation and differentiation of cardiac progenitors during heart development (10) and in cardiac remodeling (11). Consistently, inhibition of Wnt signaling significantly reduces cardiac remodeling, postinfarct mortality, and cardiac function decline (12), whereas its activation causes a progressive dilated cardiomyopathy (13,14). Thus, modulation of Wnt signaling activity might be critical for prevention of maladaptive cardiac remodeling.…”
mentioning
confidence: 95%